Risk Factors for Wound Infection after Open Appendectomy in Acute Appendicitis Patients - A Cross-Sectional Clinical Study - ASADULLA KHAWJA, MUHAMMAD; SAJJAD, MOMINA; SAJJAD, AYESHA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Open appendectomy is one of the most common surgical procedures, and surgical site infections (SSIs) are among the most common complications after open appendectomy, especially in resource constrained settings. The key predisposing factors could be identified to improve clinical outcomes and decrease postoperative morbidity. Aim: To identify the clinical, demographic, and intraoperative risk factors predictive for surgical site infections among patients undergoing open appendectomy. Methodology: A prospective clinical study was performed on 25 patients who were emergently operated for acute appendicitis through open appendectomy in the patients attending Jinnah Hospital Lahore. Demographics, comorbidities, presentation time, operative details and antibiotic administration were recorded. Incidence of SSIs in patients were followed for 30 days after the operation. Data were analyzed using SPSS version 26, p < 0.05 was regarded as significant. Results: Out of 25 patients, 7 (28%) developed surgical site infections. Delaying to presentation beyond 48 hours (p = 0.019), presence of a perforated appendix (p = 0.021), a BMI > 25 kg/m² (p = 0.041), diabetes mellitus (p = 0.029), operative time > 60 minutes (p = 0.010), and inadequate antibiotic prophylaxis timing (p = 0.035) were significant risk factors for SSIs. However, smoking was present in a higher proportion in the infected group and did not reach statistical significance (p = 0.280). Conclusion: The results of this study illustrate that the risk of SSIs after open appendectomy is elevated by the presence of clinical comorbidities, especially diabetes and the presence of obesity, late surgical intervention, perforation, and inadequate perioperative antibiotic management. Prophylactic antibiotics, early diagnosis, optimal timing of surgery are critical in minimizing postoperative wounds complications.